Vital Dimensions in Volume Perception: Can the Eye Fool the Stomach? - Raghubir, Priya; Krishna, Aradhna (Journal of Marketing Research, 1999)
Given the number of volume judgments made by consumers, for example, deciding which package is larger and by how much, it is surprising that little research pertaining to volume perceptions has been done in marketing. In this article, the authors examine the interplay of expectations based on perceptual inputs versus experiences based on sensory input in the context of volume perceptions. Specifically, they examine biases in the perception of volume due to container shape. The height of the container emerges as a vital dimension that consumers appear to use as a simplifying visual heuristic to make a volume judgment. However, perceived consumption, contrary to perceived volume, is related inversely to height. This lowered perceived consumption is hypothesized and shown to increase actual consumption. A series of seven laboratory experiments programmatically test model predictions. Results show that perceived volume, perceived consumption, and actual consumption are related sequentially. Furthermore, the authors show that container shape affects preference, choice, and postconsumption satisfaction. The authors discuss theoretical implications for contrast effects when expectancies are disconfirmed, specifically as they relate to biases in visual information processing, and provide managerial implications of the results for package design, communication, and pricing.